Segmentation In Medical Resonance images to extract the cancerous nodule for early diagnosis on cancer - Brar, Raman (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
<span id="internal-source-marker_0.3248950551122224" style="color: #000000; font-family: 'Times New Roman'; font-size: 16px; font-variant: normal; text-decoration: none; vertical-align: baseline; background-color: transparent;">Image segmentation plays a vital role in several medical imaging programs by assisting the delineation of physiological structures along with other parts. The objective of this research work is to segmentize human lung MRI (Medical resonance Imaging) images for early detection of cancer.Watershed Transform Technique is implemented as the Segmentation method in this work. Some comparative experiments using both directly applied watershed algorithm and after marking foreground and computed background segmentation methods show the improved lung segmentation accuracy in some image cases.